Reactivity of Aryl Halides for Reductive Dehalogenation in (Sea)water Using Polymer-Supported Terpyridine Palladium Catalyst - Toshimasa Suzuka; Hiromu Sueyoshi; Shohei Maehara; Hiroaki Ogasawara (Molecules, 2015)
A polymer-supported terpyridine palladium complex was prepared. The complex was found to promote hydrodechlorination of aryl chlorides with potassium formate in seawater. Generally, reductive cleavage of aryl chlorides using transition metal catalysts is more difficult than that of aryl bromides and iodides (reactivity: I > Br > Cl); however, the results obtained did not follow the general trend. Therefore, we investigated the reaction inhibition agents and found a method to remove these inhibitors. The polymeric catalysts showed high catalytic activity and high reusability for transfer reduction in seawater.